The role of soft skills and multicultural attitudes in enhancing teaching quality in Colombian higher education. - Fernando Barrios Aguirre; Susan Benavides Trujillo; Edgar Iván Vega Guillén; Fernando Alonso Téllez Mendivelso (PLoS ONE)
This paper will explore whether teachers' multicultural ideology, soft skills (transversal capacities), national pride and identity, and intergroup contact, controlled by other variables, are related to their multicultural attitudes. This objective is developed and estimated from correlation analysis and using the method of ordinary least squares, to verify how multicultural ideology, national pride and identity, soft skills, and intergroup contact, controlled for some sociodemographic variables, generate effects on the multicultural attitudes of teaching in a Colombian higher education institution with high-quality accreditation. The findings revealed that soft skills and multicultural ideology positively influenced teachers' multicultural attitudes, while intergroup contact with different ethnic groups showed a negative correlation. The analysis used primary data collected from 199 professors at the institution, which operates in a culturally diverse, multi-campus context within an emerging country characterized by very low national pride.